Effect of Co on twin formation and magnetic properties of Sm(Fe,Ti,V)12 alloys - Tozman, P; Hrkac, G; Patrick, CE; Staunton, JB; Saito, T; Sasaki, T; Ohkubo, T; Sepehri-Amin, H (Elsevier, 2024)
Transferring the excellent intrinsic magnetic properties of SmFe12-based compounds to their extrinsic properties remains the main challenge in the development of high-performance SmFe12-based permanent magnets. Twin formation is one of the reasons for the inability to achieve high coercivity and remanence. Here we have shown that the addition of Co in Sm(Fe1-xCox)10–11M1–2 alloys, where M=Ti and V, leads to an increase in twin density. Microstructural characterizations revealed that the atomic arrangement in the twin boundary changes depending on the stabilizing element, which directly influences the local intrinsic magnetic properties. Theoretical investigations showed that the critical grain size at which twin formation can be hindered by grain size reduction decreases when the stabilizer changes from V to Ti. This study shows that the alloy composition influences not only the intrinsic magnetic properties but also the twin formation energy and its grain size dependence, crucial for the design of SmFe12-based permanent magnets.